2021
DOI: 10.4049/jimmunol.2001299
|View full text |Cite
|
Sign up to set email alerts
|

Coformulation with Tattoo Ink for Immunological Assessment of Vaccine Immunogenicity in the Draining Lymph Node

Abstract: Characterization of germinal center B and T cell responses yields critical insights into vaccine immunogenicity. Nonhuman primates are a key preclinical animal model for human vaccine development, allowing both lymph node (LN) and circulating immune responses to be longitudinally sampled for correlates of vaccine efficacy. However, patterns of vaccine Ag drainage via the lymphatics after i.m. immunization can be stochastic, driving uneven deposition between lymphoid sites and between individual LN within large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Interestingly, we also confirmed an uptake of tattoo ink by lymphocytes as reported before by other groups where the authors demonstrated that although tattoo ink was located in lymph nodes, it did not affect the responses of B and T cells [19]. Moreover, the uptake by granulocytes might be low, but due to their high numbers, it might be important as well.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we also confirmed an uptake of tattoo ink by lymphocytes as reported before by other groups where the authors demonstrated that although tattoo ink was located in lymph nodes, it did not affect the responses of B and T cells [19]. Moreover, the uptake by granulocytes might be low, but due to their high numbers, it might be important as well.…”
Section: Discussionsupporting
confidence: 91%
“…It should also be noted that we analyzed only inguinal LNs near the site of vaccination. Recent findings suggested that drainage of antigen to inguinal LNs could be variable following IM immunization, while iliac lymph nodes showed better drainage 34 . Generally, the antigen is drained more to LNs that are closest to the site of vaccination, and thus IM immunizations may target deeper LNs compared to ID immunizations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was the prolonged immunogen release that yielded the greatest increase in GC activity and downstream nAb development, though further dose-matched comparisons and an understanding of how well Evans Blue (a small molecule dye) recapitulates formulated vaccine antigen draining is needed. A more recent study has proposed tattoo ink as an alternative for identifying the antigen draining lymph nodes within a lymph node cluster ( 40 ).…”
Section: Non-human Primatesmentioning
confidence: 99%